Pengaruh Iklan dan Promosi Harga Terhadap Ekuitas Merek dan Dampaknya Pada Keputusan Pembelian Mobil - Moch Syauki; Lukman Lukman (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2019)
The research is empirical studies that aims to understand the influence of advertising and promotion of brand equity to the price and its impact on the decision of the purchase of car toyota brand in the city of banda aceh. The population of research every consumer brands toyota car users in the city of banda aceh in 2018 a total of 150 people. The withdrawal of the sample in this research done with at least by using a formulation of the sample sevila slovin and consumers and the sample is 109. Data collection done by distributing the questionnaire. The primary data analyzed by an analysis of the device SPSS with the assistance.The research results show that advertising it has some positive effects and significantly to brand equity. The promotion of the price it has some positive effects but not significantly to brand equity. Advertising it has some positive effects and significant of the decision of the purchase. The promotion of the price it has some positive effects and significant of the decision of the purchase. Brand equity can enhance the role of the influence of advertising and promotion the price of the decision of the purchase.